Factors Affecting Decision to Have Vacation on Sri Gethuk Waterfall Gunungkidul - Ignatius Soni Kurniawan (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
This paper examines the effect of cultural factor, social factor, and personal factor toward purchasing decision on tourist attractions. The sample was taken by applying a non-probability method with a accidental sampling technique. The questionnaires processed were 100 in number. The data were analyzed by making use of multiple linear regression technique. The finding showed that there was no significant effect cultural factor and personal factor toward purchase decision, but there was significant and positif effect social factor toward purchase decision.